2012
DOI: 10.1386/iscc.2.1.17_1
|View full text |Cite
|
Sign up to set email alerts
|

‘I don’t wanna be anything other than me’: A case study on gender representations of teenagers in American teen drama series One Tree Hill

Abstract: Keywordsgender stereotypes representations sexuality teenagers teen series elKe Van damme and sofie Van Bauwel Ghent University 'i don't wanna be anything other than me': a case study on gender representations of teenagers in american teen drama series One Tree Hill aBstract Economic and demographic trends have turned young people into a target audience, and media producers and the marketing industry have realized that the contemporary teenage market has substantial potential. Television is still the most popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…At the same time, they represented the teens’ sexual identity formation as an individualized struggle, disconnected from broader sociocultural processes that sustain gender and sexual inequalities. Similarly, Elke Van Damme and Sofie Van Bauwel (2012) and Wendy Peters (2016) argued that many teen series were rooted in heteronormativity, informing the representation of heterosexuality and nonheterosexuality. For instance, Elizabeth Crowley Webber (2019) found that LGBTQ teens were encouraged to identify as nonheterosexual in the series’ narratives but were never represented as having sex or expressing same-sex intimacy.…”
Section: Sexual Identity Formation Lgbtq Representation and Teen Dramamentioning
confidence: 99%
“…At the same time, they represented the teens’ sexual identity formation as an individualized struggle, disconnected from broader sociocultural processes that sustain gender and sexual inequalities. Similarly, Elke Van Damme and Sofie Van Bauwel (2012) and Wendy Peters (2016) argued that many teen series were rooted in heteronormativity, informing the representation of heterosexuality and nonheterosexuality. For instance, Elizabeth Crowley Webber (2019) found that LGBTQ teens were encouraged to identify as nonheterosexual in the series’ narratives but were never represented as having sex or expressing same-sex intimacy.…”
Section: Sexual Identity Formation Lgbtq Representation and Teen Dramamentioning
confidence: 99%